HRM and change management. Comparative results from three European cities of excellence. - Salm, Marco; Schwab, Christian (My University, 2015)
Das Papier beleuchtet am Beispiel dreier mit dem European Public Sector Award ausgezeichneten Städte die Zusammenhänge zwischen Verbesserungen im Personalmanagement in der öffentlichen Verwaltung und Change Management.

In this paper published by the Deutsches Forschungsinstitut für öffentliche Verwaltung Speyer, Marco Salm and Christian Schwab examine the role of HRM in public management reform in the Cities of Bilbao, Mannheim and Tampere - all three former EPSA winners, nominees or awarded best practices. This publication provides some insights on the correlation between change management and HRM reforms and their (presumed) effects. Thus, it contributes to compiling evidence on the effect of reforms and role of HRM at the local government level.
Keywords: Verwaltung; Verwaltungsreform; Personalwesen; Öffentliche Verwaltung; Change Management